KEKUATAN DAN KELEMAHAN PELAKSANAAN MICROTEACHING DI LAB. PEMBELAJARAN FMIPA UNIVERSITAS NEGERI SURABAYA - Endang Susantini; Ulfi Faizah; Abdul Kholiq; Bertha Yonata; An Nuril Maulida (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The purpose of this research to describe the strength and the weakness factors from microteaching activities which held in Mathematics and Science Faculty Laboratory, Surabaya State University. This descriptive research use in-depth interview technique and questionnaire. The data were obtain from 25 lecturers of Field Experience I Subject, 100 students who already take this program and also 15 learning laboratory crew on Mathematics and Science Faculty. The result of this research report that: (1) The strength of microteaching activities in Mathematics and Science Faculty werelean on the lecturers who doing shooting and editing by him/herself which already trained through workshop, and video learning of the result microteaching used by student and lecturer for reflections, (2) The weakness of microteaching activities in Mathematics and Science Faculty were the quality of result microteaching video should be improve. Keywords: microteaching, Mathematics and Science Faculty State University of Surabaya